SOSIALISASI INTERNET SEHAT DAN AMAN PADA SISWA SMP N 2 KEMBARAN - Shodiq Khalidy; Waidi; Luzi Dwi Oktaviana (Yayasan Nusantara Hasana Berdikari, 2023)
Internet use in Indonesia in 2021 has reached around 202.6 million users, the internet has been used by all groups, including parents, teenagers and children. The use of the internet has both positive and negative impacts on its users depending on the user's usage. The use of the internet among students is very necessary to help the learning process, but many students of SMP N 2 Kembaran still use the internet only to access social media and online games. Therefore, to minimize the negative impact of using the internet for SMP N 2 Kembaran students, it is necessary to socialize the use of the internet in a healthy and safe manner. In order to run well, this community service activity is carried out in 3 stages, namely the preparation stage, the implementation stage and the evaluation stage. The socialization will be held on June 10, 2023, starting from 08.00 WIB to 11.00 WIB. Based on the evaluation stages, it can be concluded that after socialization on healthy and safe internet use, students understand healthy internet tips, threats on the internet, self-protection from phishing and cyberbullying alert.